(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
As a result of the transition of the higher education system of our country to the credit-module system, great changes have been made in this system. Decree No. PF-5953 dated March 2, 2020 of the Cabinet of Ministers of the Republic of Uzbekistan on measures to improve the system related to the organization of the educational process in higher education institutions "2020/2021 academic year It is said that the procedure for gradually transferring the educational process to the credit-module system should be introduced in higher educational institutions of the republic starting from 2016. In this system, the percentage of hours allocated to independent work of students has been increased.